Risk Analysis of Steel Railway Bridges Based on Rating Factor, Earthquake, and Importance Factor - Prasetyo, Aulia Azis; Triwiyono, Andreas; Supriyadi, Bambang (ASTONJADRO, 2025)
Railway bridges are critical infrastructure components that are essential to support and maintain the integrity of major rail transportation networks. Indonesia is located in a tectonic zone known as the Ring of Fire. Risk assessment of these bridges is critical. This research not only considers the physical condition or vulnerability of the bridge itself but also the risk posed by earthquakes and the level of importance of the bridge. The research was conducted on 4 bridges located in East Java Province, namely the BH-129, BH-262, BH-275, and BH-314 Bridges. The rating factor, hazard level, and importance factor influence the risk level. The assessment process starts by using the Bridge Management System (BMS) method and Structure Analysis Program (SAP2000) to assist in calculating the Rating factor. Determining the level of danger by referring to the Earthquake Hazards Map and the Indonesian Earthquake Code (SNI 2833: 2016), The importance is taken based on the level of operational importance of the bridge referring to the same standard. The results show that the four bridges have the same risk value of 0.7809 for each bridge. The results underscore the urgent need for proactive measures to reduce the potential adverse impacts of bridge structure failure. Recommended interventions include strengthening structural elements, increasing inspection frequency, improving maintenance protocols, and, if necessary, replacing compromised structures. These strategies are critical due to the high risk and significant impact on rail safety and operations, especially in areas prone to natural disasters. The results of this study reinforce the urgency of improving the resilience of bridge infrastructure to earthquake threats to maintain the stability and safety of rail transportation in Indonesia.